2015
DOI: 10.1371/journal.pntd.0003893
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Granulomatous Inflammation and Prophylactic Treatment of Schistosomiasis with a Combination of Edelfosine and Praziquantel

Abstract: BackgroundSchistosomiasis is the third most devastating tropical disease worldwide caused by blood flukes of the genus Schistosoma. This parasitic disease is due to immunologic reactions to Schistosoma eggs trapped in tissues. Egg-released antigens stimulate tissue-destructive inflammatory and granulomatous reactions, involving different immune cell populations, including T cells and granulocytes. Granulomas lead to collagen fibers deposition and fibrosis, resulting in organ damage. Praziquantel (PZQ) is the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 92 publications
3
40
0
1
Order By: Relevance
“…The finding that edelfosine diminishes the capacity of macrophages to mount an inflammatory response might be relevant, as severe inflammation at the site of infection leads to tissue destruction in leishmaniasis [ 60 ]. In this regard, edelfosine has also been reported to display a potent anti-inflammatory action through L-selectin shedding in human neutrophils, thus preventing neutrophil extravasation [ 31 ], and recent in vivo evidence further supports the anti-inflammatory and immunomodulatory effect of edelfosine [ 61 63 ]. Furthermore, edelfosine promotes apoptosis in mitogen-activated T lymphocytes [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…The finding that edelfosine diminishes the capacity of macrophages to mount an inflammatory response might be relevant, as severe inflammation at the site of infection leads to tissue destruction in leishmaniasis [ 60 ]. In this regard, edelfosine has also been reported to display a potent anti-inflammatory action through L-selectin shedding in human neutrophils, thus preventing neutrophil extravasation [ 31 ], and recent in vivo evidence further supports the anti-inflammatory and immunomodulatory effect of edelfosine [ 61 63 ]. Furthermore, edelfosine promotes apoptosis in mitogen-activated T lymphocytes [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, we acknowledge that there is considerable variation reported in number and speed of centrifugations, as well as gradient concentrations used in protocols to isolate liver leukocytes. 11,13,28,29 Nevertheless, our data suggest that careful optimization of these methods will be required for studies where KCs are the major cell of interest.…”
Section: Isolation Methods Can Lead To Selective Loss Of Kcsmentioning
confidence: 97%
“…Thus, edelfosine has been found to promote apoptosis in activated lymphocytes (Cabaner, et al, 1999), hence suggesting a role for this drug in the treatment of autoimmune diseases (Abramowski, et al, 2014;Mollinedo, 2007). In addition, in vitro and in vivo assays in animal models have shown that edelfosine is a potent anti-inflammatory agent , as well as an effective drug against leishmaniasis Varela, et al, 2012) and schistosomiasis (Yepes, et al, 2014;Yepes, et al, 2015). Additional biomedical applications and patents for…”
Section: Clinical Perspectivesmentioning
confidence: 99%